EVALUATING GENDER RESPONSIVE PUBLIC POLICIES: A SYSTEMATIC REVIEW OF IMPLEMENTATION AND OUTCOMES IN ASEAN MEMBER - Hatta Ridho; Muhammad Azhar Nasution; Randa Putra Kasea Sinaga; Gusti Pirandy; Mujahid Widian Saragih (Social Studies and Humanities Journal (SOSHUM), 2025)
This study evaluates the implementation and outcomes of gender-responsive public policies across ASEAN member states. Despite progress in certain areas, significant challenges persist in policy execution and impact. The research systematically reviews gender-sensitive initiatives, highlighting factors such as socio-cultural influences, administrative mechanisms, and policy enforcement gaps. Using analytical tools like gender disaggregated expenditure incidence analysis (EIA), the study examines how public spending affects gender equality. Findings indicate that while policies promoting women’s participation such as gender quotas show promise, entrenched patriarchal norms and systemic barriers hinder progress. Furthermore, gender disparities in healthcare and economic participation remain critical issues, especially during crises like COVID-19. The study emphasizes the need for cross-sectoral collaboration, inclusive policymaking, and continuous evaluation to enhance the effectiveness of gender-responsive policies in ASEAN. Strengthening institutional frameworks and addressing socio-cultural resistance are essential to achieving sustainable gender equality in the region.